THE ORGANIZATION OF AN ENGLISH ENTRANCE TEST TO MA COURSE: LINGUAL AND DIDACTIC ASPECT - Lastovka, Krystyna I. (Educological discourse, 2014)
This article focuses on the analysis of fundamental moments at making an English entrance test to MA course for students of non-lingual specialities. The article also contains recommendations on preparing students for testing control of their receptive skills and theses for developing a lingual test as a means of intensification of methodical erudition of specialists-examiners.